'Learning to bring dead capital to life': the Riksens Ständers Bank and the credit market in seventeenth-century Sweden. (August 2019) - Pihl, Christopher
Abstract: Successful mortgage lending is often said to require a system of registration, which records the ownership of, and any encumbrances on, a particular piece of real estate. Here we analyse how Sweden's Riksens Ständers Bank handled the uncertainties of the mortgage lending market c. 1680–1700, when there was no coherent system of property registration. The bank tried to make registration compulsory, but when influential groups opposed this move, the bank had to modify its lending practices. The study thus sheds light on the somewhat fraught initial stages of the shifts in the credit system, which from the latter half of the seventeenth century onwards, saw personal trust replaced by system trust, and private credit replaced by institutional credit. French Abstract: On dit souvent que le succès d'un prêt hypothécaire repose sur un bon système d'enregistrement de la propriété d'un bien immobilier, y compris les charges qui en découlent précisément. Nous analysons comment la banque suédoise Riksens Ständers a géré les incertitudes touchant le marché du crédit hypothécaire entre 1680 et 1700 environ, alors qu'il n'existait aucun système cohérent d'enregistrement de la propriété. Cette banque a tenté de rendre cet enregistrement obligatoire, mais les groupes d'influence se sont opposés à ce changement, et elle a dû modifier ses pratiques de prêt. L'article éclaire par quels chemins tortueux le système de crédit put être modifié, menant, à partir de la seconde moitié du dix-septième siècle, à remplacer confiance en une personne par confiance dans un système, crédit privé se trouvant remplacé par crédit institutionnel. German Abstract: Nach landläufiger Auffassung erfordern Hypothenkreditgeschäfte ein Register, in dem die Eigentumstitel und Belastungen jedes einzelnen Grundstücks verzeichnet sind. In diesem Beitrag wird analysiert, wie die schwedische Riksens Ständers Bank mit den Unsicherheiten des Hypothekenkreditmarktes im Zeitraum von zirka 1680–1700 umging, als es noch kein kohärentes System der Grundstücksregistrierung gab. Die Bank versuchte, die Registrierung verpflichtend zu machen, aber als einflussreiche Gruppen sich diesem Schritt widersetzten, musste sie ihre Kreditvergabepraktiken modifizieren. Die Untersuchung beleuchtet somit die ziemlich angespannten Anfangsstadien in der Entwicklung des Kreditsystems, in denen ab dem späten 17. Jahrhundert das persönliche Vertrauen durch Vertrauen ins System und der private Kredit durch institutionellen Kredit ersetzt wurde.